Compartment Syndrome of the Hand in Multiple Metacarpal Fractures: A Case Report and Review of Literature - G, Kastanis; MR, Siligardou; P, Ioannou; C, Chaniotakis; A, Tsioupros; I, Ktistakis; P, Kapsetakis; I, Stavrakakis (An Overview of Disease and Health Research Vol. 2, 2025)
Metacarpal fractures are the most common injuries in the emergency department and account for to17.2% of all adults’ fractures and more than 30% of all hand injuries. The majority of these cases are stable injuries and conservative treatment with closed reduction and immobilisation offers both good clinical and functional outcomes. Compartment syndrome of the hand is an urgent pathological condition which produces irreversible changes to the neurovascular supplies of the hand and may lead to ischemia, permanent loss of hand functions or amputation. The purpose of this study is bimodal: Firstly, to present two cases which presented in the emergency department of our unit, after a traffic accident, with multiple metacarpal fractures and developed acute syndrome of the hand. Based on this condition, a theoretical question should be answered: Do multiple metacarpal fractures increase the risk of acute syndrome of the hand? Secondly, develop a sense of suspicion of this kind of lesion in physicians in the emergency department with a scope to the precocious diagnosis and treatment. While multiple metacarpal fractures may be a responsible factor, the emphasis must be placed on the mechanism and energy of injury, as well as the adequacy of early management, in assessing the risk of compartment syndrome.